Carta de Manuel F. Rossy a Roberto H. Todd - Todd, Roberto H.; Rossy, Manuel F. (My University, 1921)
Situación de los separatistas en las cámaras legislativas y en el Partido Unión de Puerto Rico.
Keywords: Partido Unión de Puerto Rico; Partido Republicano (Puerto Rico); Republican party. Puerto Rico.; Coll y Cuchí, Cayetano, 1881-1961; Córdova Dávila, Félix, 1878-1938